Data-Informed Program Planning for Academic Chairs and Directors - Laurie Henry; Richard Wilkens (Academic Chairpersons Conference Proceedings, 2019)
Presenters and participants will engage in conversations related to data-informed decision making for academic departments and programs. Emerging strategies and best practices in data analysis will be employed to address critical questions related to cost efficiency, enrollment trends, and faculty load at the program level.
Keywords: data informed decision making; program planning; cost efficiency; enrollment trends; faculty load